2017
DOI: 10.1021/acs.nanolett.7b01348
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of a Two-Dimensional PbSe Square Superstructure in an Electrolyte-Gated Transistor

Abstract: Self-assembled nanocrystal solids show promise as a versatile platform for novel optoelectronic materials. Superlattices composed of a single layer of lead–chalcogenide and cadmium–chalcogenide nanocrystals with epitaxial connections between the nanocrystals, present outstanding questions to the community regarding their predicted band structure and electronic transport properties. However, the as-prepared materials are intrinsic semiconductors; to occupy the bands in a controlled way, chemical doping or exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…The mobilities reported for SL‐EDA samples are obtained from two substrates, as shown by the different colors in Figure f, with average mobility of 12 and 15 cm 2 V −1 s −1 . The values obtained for the non‐EDA superlattices are comparable to those reported by Alimoradi Jazi et al, while the EDA‐based ones (averaged on either substrate) are the highest ever reported for quantum confined lead‐chalcogenide superlattice samples.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The mobilities reported for SL‐EDA samples are obtained from two substrates, as shown by the different colors in Figure f, with average mobility of 12 and 15 cm 2 V −1 s −1 . The values obtained for the non‐EDA superlattices are comparable to those reported by Alimoradi Jazi et al, while the EDA‐based ones (averaged on either substrate) are the highest ever reported for quantum confined lead‐chalcogenide superlattice samples.…”
supporting
confidence: 85%
“…This possibility stems from the faceted nature of the CQDs; crystal orientation‐specific interactions and different binding energy of the ligands at the main crystallographic facets drive the orientation process . While much work has been done on the formation mechanism and properties of the superlattices on solid substrates, fewer studies investigated liquid interface‐grown layers, and even fewer have been devoted to study the structure–property relation in these samples . Whitham et al measured the effect of disorder on charge localization in PbSe CQD superlattices, they deduced a carrier localization over two to three quantum dots in their system and calculated a disorder limit below which band‐like, coherent transport is expected to occur .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This avoids the introduction of Br À and SCN À ion impurities into the sample (which occur with the tetrabutylammonium bromide and ammonium thiocyanate treatments, respectively) that could potentially be problematic in some scenarios and applications. We anticipate that the PbSe nanocrystal films with SnSe-like interstitial material in this work could be promising for thin film transistors, [42,43] and optoelectronics. [44][45][46][47] PbSe is also an excellent thermoelectric material [48,49] and Sn-alloyed PbSe can function as topological crystalline insulator.…”
Section: Treatment Of Pbse Nanocrystal Thin Films With Tin(iv) Methylmentioning
confidence: 95%
“…Optimizing the method, superlattice domains of several micrometers can be achieved, and the properties of the structures can be studied. The interest in these structures has recently been validated by two works reporting record charge carrier mobilities in PbSe CQD superlattices, with a clear improvement compared to what is found in traditional disordered arrays …”
Section: Assembly Of Cqd Thin Filmsmentioning
confidence: 99%